(Re)Formasi Birokrasi: Profesionalisme Birokrat pada Level Perguruan Tinggi - Buntari Buntari (DIMENSI - Journal of Sociology, 2017)
This article is meant to discus bureaucrate professionalism issue in national bureaucrate framework, particularly in university revitalization context. It was urgent to think how national discourse placed university proportionate with bureaucracy professionalism discourse and bureaucracy reformation in another side except as a post new order’s mandate. This became urge necessity to accelerate nasional development which based on human resource excalation. Thus, education bureaucracy affairs especially at the university level is emphasized in this article. By using descriptive method, the research took case in state universities in Jember region. The results showed that there was bureacracy professionalism discourse which had been interpreted differently at local and personal level. The interpretation developed into discussion and bureaucrate practices in social sphere which culturally formed whereas the social sphere could blur categories between status and roles that structurally tied individual bureaucrate.